Research profile and bibliography of Professor Łucja Biel - Koźbiał, Dariusz (Comparative Legilinguistics, 2023)
This article consists of two sections. The first outlines the research profile of Dr hab. Łucja Biel, Prof. ucz., a Polish linguist recognised nationwide and internationally who specializes in the analysis of legal varieties of Polish and English in the context of legal translation studies, corpus linguistics and translator training. The second part contains a detailed list of publications (co-)authored or co-edited by Łucja Biel and published between 2004 and 2022.